Conceptualization of colours in the language of congenitally blind persons and the ones who became blind in the early stage of development - Jęczeń, Urszula (Logopedia Silesiana, 2023)
The subject of the paper is the way of conceptualization, linguistic depiction of the names of colours by adult persons who were born blind and the ones who became blind at the age of 3–5 and kept some visual images in their memories. The material for the study was obtained by conversations via phone. The respondents were nine randomly chosen members of a Facebook group “The blinds and the visually impaired ones – let’s be together!”, namely 4 women and 5 men. As the results of the study show, the extent and way of using other senses for describing colours depends on the moment when the sight was lost. The congenitally blind people defined the colours relying on the senses of smell and touch rather than sound, while the ones who became blind in the early childhood find the sense of taste the most helpful and the sense of smell the least useful in that.